2007
DOI: 10.1136/adc.2006.107375
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathogenesis of congenital anomalies in cerebral palsy

Abstract: Congenital anomalies in children with CP are found much more frequently than expected by chance. A common pathogenic mechanism may account for the coexistence of disparate congenital anomalies. A hypothesis is proposed for such a common pathogenic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
4
35
3
Order By: Relevance
“…[18][19][20][21] A study based on the CP Register and the Birth Defect Registry of Western Australia reported that 15.8% of children with CP had non-CNS anomalies. 19 Pharaoh 21 demonstrated an increase in eye anomalies, cardiac anomalies, cleft lip and ⁄ or palate, congenital dislocation of the hip and talipes, and atresias of the oesophagus and intestines in children with CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] A study based on the CP Register and the Birth Defect Registry of Western Australia reported that 15.8% of children with CP had non-CNS anomalies. 19 Pharaoh 21 demonstrated an increase in eye anomalies, cardiac anomalies, cleft lip and ⁄ or palate, congenital dislocation of the hip and talipes, and atresias of the oesophagus and intestines in children with CP.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Different hypotheses are postulated for this linkage. One theory is that congenital non-CNS malformations and CP are a result of the same maternal cause.…”
Section: Discussionmentioning
confidence: 99%
“…CP is caused by damage to the motor control and cognitive centers of the developing brain and can occur during pregnancy (approximately 75%), during childbirth (approximately 5%), or after birth (approximately 20%; Thorngren-Jerneck & Herbst, 2006). The incidence of CP is approximately 2 per 1,000 live births in industrialized countries; incidence is higher in boys than in girls (Pharoah, 2007;Strauss, Brooks, Rosenbloom, & Shavelle, 2008).…”
mentioning
confidence: 99%
“…[30][31][32] In 3 Class III (n ϭ 338) studies, the combined prevalence of congenital and postnatal onset microcephaly ranged from 32.5% to 81% and averaged 47.9%. [33][34][35] In one of these studies (n ϭ 96), 68% were diagnosed with postnatal onset microcephaly and 13% had congenital microcephaly.…”
mentioning
confidence: 99%